Education for Prospective Teachers on Augmented Reality (AR) Learning Media in Science Subjects - Darusman Darusman; Alya Puspita Zahra; Muttaqiin Muttaqiin; Shelly Efwinda; Zeni Haryanto (Universitas Lambung Mangkurat, 2024)
The improvement of education quality can be supported by the utilization of technology such as Augmented Reality (AR) as a learning media that can help teachers visualize the material. Prospective teachers need to understand the benefits of using AR as a learning media and be motivated to realize it. This education activity aims to increase the knowledge of prospective science teachers regarding the utilization of AR as a learning media and how to create it. The target participants in this education activity are prospective science teacher students from various universities in Indonesia. The participants who attended this education activity were 115 prospective science teacher students from several universities in Indonesia. Data collection of participant responses used a questionnaire consisting of 10 statements and one open-ended question regarding the participants' messages and impressions of this education activity. Participants gave very good responses, averaging 82% towards this activity. These response results indicate that this education activity achieved its goals in terms of the number of participants and the types of responses from participants. Participants are interested in this activity and motivated to practice creating AR media.